2002
DOI: 10.1111/j.1752-1688.2002.tb04349.x
|View full text |Cite
|
Sign up to set email alerts
|

HEALTH RISKS ASSOCIATED WITH CONSUMPTION OF UNTREATED WATER FROM HOUSEHOLD ROOF CATCHMENT SYSTEMS1

Abstract: Rainwater harvesting is receiving increased attention worldwide as an alternative source of drinking water. Although collected rainwater is typically consumed without any type of disinfection, the microbial quality of this type of water source can be poor. Around the world, consumers of collected and stored rainwater may be at considerable risk to a variety of infectious diseases. This review presents studies attributing specific risks of diseases to the consumption of contaminated rainwater. Diseases attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(74 citation statements)
references
References 24 publications
2
64
1
7
Order By: Relevance
“…Studies by Ref. [30,31] have associated use of water of poor quality to the transmission of infectious diseases such as diarrhea, cholera and skin diseases in the tropics. There is need to conduct environmental health education and promote appropriate family planning methods in Bufundi sub county to reduce the risk of exposure to environmental related diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Ref. [30,31] have associated use of water of poor quality to the transmission of infectious diseases such as diarrhea, cholera and skin diseases in the tropics. There is need to conduct environmental health education and promote appropriate family planning methods in Bufundi sub county to reduce the risk of exposure to environmental related diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Despite having some promising merits over other sources, rainwater use has frequently been rejected as a source of potable water supply on the grounds of its water quality concerns (Meera and Ahammed, 2006). As reported by several researchers harvested rainwater can contain significant amounts of pollutants such as heavy metals, nutrients and pathogens (GromaireMertz et al, 1999;Lye, 2002;Zhu et al, 2004;Evans, 2006;Yufen et al, 2008). Thus in determining the end use and the potential success of potable use of rainwater in the study area, the possible problems associated with its quality need to be assessed.…”
Section: Ezemonye Mn; Isueken Co; Emeribe Cnmentioning
confidence: 99%
“…Research into the quality of harvested rainwater and health risks associated with potable and nonpotable end uses has been undertaken in a range of contexts (Lye, 2002;CRC, 2005;Meera and Ahmed, 2006;Fewtrell and Kay, 2007a;Ahmed et al, 2011;Ward, 2010 andde Kwaadsteniet et al, 2013). This is in recognition that although rainwater generally does not contain many contaminants, except those derived from the atmosphere, once it is harvested and stored the quality may deteriorate, particularly from a microbiological perspective, due to a range of variables.…”
Section: Introductionmentioning
confidence: 99%
“…Sources of contamination from the catchment can include wind-blown particulates and animal and bird faeces, which have particular implications for microbiological quality, leading to potential health risks (WHO, 2008). Lye (2002) reviewed a number of studies across the USA, Australia, Thailand and Micronesia between 1983 and 1996 and concluded that whilst some RWH systems were prone to containing high levels of faecal coliforms others were not, highlighting the site-specific nature of harvested rainwater quality. This was reinforced by the Australian Cooperative Research Centre for Water Quality and Treatment (CRC, 2005), Fewtrell and Kay (2007a), Meera and Ahmed (2006) and more recently by Ahmed et al (2011) who undertook a review of studies in similar contexts between 1978 and 2009 linking the microbiological quality of harvested rainwater and health risks.…”
Section: Introductionmentioning
confidence: 99%